Seller and Buyer Integrated Forms of Indonesian and Tetun Language in Pasar Baru Betun, Central Malaka, Malaka Province - Vincentius Mauk; Nadya Afdholy (ENLIT, 2021)
The ability of the Tetun community to use two languages ​​or bilingual will give birth to the transfer or transition of languages. In the transition or transfer of language, two very important things will emerge, namely positive and negative transfers. Negative transfers will cause interference and positive transfers will lead to integration. Integration arises from positive transfer because it benefits both languages ​​from the donor language into the recipient language or the absorbing language. The recipient's language is Tetun and the granting language is Indonesian. The purpose of this study is to determine the forms of language integration Indonesian into Tetun in the conversation of traders and buyers in Pasar Baru Betun, Central Malaka Sub-District, Malaka District. The researcher focused on the integration of Indonesian into Tetun. This type of research is qualitative research, the technique used in collecting data is the technique of record, see and interview. The results of this study indicate that the integration of the Indonesian language into Tetun is in the form of basic words, affixation, reduplication, composite and abreviation (shortening of words).